2014
DOI: 10.1590/s0102-67202014000100009
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision videolaparoscopic appendectomy with conventional videolaparoscopy equipment

Abstract: BackgroundAcute appendicitis is the most common surgical emergency in daily practice, and is approached laparoscopically in many centers. Efforts have been undertaken for the development of minimally invasive techniques that reduce tissue trauma and offer improved cosmetic results, one of such being the single-incision laparoscopic surgery (SILS).AimTo present a minimally invasive technique for appendectomy (SILS) undertaken with conventional instruments.MethodEleven patients were treated in the emergency care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…13 Successful operations using DILA urged the push for SILS, as stated previously, primarily for cosmetic reasons. 11 In direct comparison to traditional laparoscopic appendectomy, SILS appendectomy can be conducted with comparable operative times, lengths of stay, and procedural complications, and with superior cosmetic outcomes -the main downside noted being the cost. 14,15 As reported in this case, the use of SILS can be easily manipulated using conventional laparoscopic instruments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13 Successful operations using DILA urged the push for SILS, as stated previously, primarily for cosmetic reasons. 11 In direct comparison to traditional laparoscopic appendectomy, SILS appendectomy can be conducted with comparable operative times, lengths of stay, and procedural complications, and with superior cosmetic outcomes -the main downside noted being the cost. 14,15 As reported in this case, the use of SILS can be easily manipulated using conventional laparoscopic instruments.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study outlined SILS appendectomy utilizing three trocars (two 10mm and one 5mm), using conventional and optical laparoscopic tweezers (10 mm, 30˚); while using titanium LT 400 clips to ligate the base and pedicle of the appendix. 11 As described earlier, the SILS procedure can be applied to appendectomy in female patients suffering from endometriosis. A previous study performed to evaluate deeply located endometriosis showed significant involvement of the appendix.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The technique of single umbilical access is feasible for the appendectomy, and has better aesthetic appeal in relation to the multiple visible incisions in the abdominal wall 8 , 11 , 14 , 17 , 24 , 25 , 26 , 29 . The incisional access needs to be wider, and may become visible or can deform the patient's umbilicus.…”
Section: Discussionmentioning
confidence: 99%